(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: In this study forty patients of sinonasal malignancy were studied to observe the topographical distribution of the disease. Methods: This cross sectional study was done in the Otolaryngology-Head & Neck Surgery Department of Bangabandhu Sheikh Mujib Medical University during the period of January 2007 to December 2008. The diagnosis was made by detailed history, clinical examination, investigation. Analyzed data presented by various tables, graphs and figures. Results: In this study majority of the patients were within 51-60 years of age. Male to female ratio was 3:1 and came from rural area (62.5%). Most of them were farmers (37.5%), illiterate (35%), poor socioeconomic condition (55%) and habits were smoker (37.5%). Most of the patients presented with multiple symptoms and multiple sinuses involvement (70%) and among single sinus involvement maxillary (58.34%) followed by nasal cavity (33.33%), ethmoidal sinuses (8.33%), primary frontal and sphenoid tumours were not found. About T stage of tumour T3 (42.5%), T4 (37.5%), T2 (15%) and T1 (5%). 08 cases were nodal involvement (20%), submandibular node metastasis were most common (62.5%), squamous cell carcinoma (55%), followed by adenocystic carcinoma (10%). Adenocarcinoma (7.5%), mucoepidermal carcinoma (5%), non Hodgkin’s lymphoma (5%), transitional cell carcinoma (5%), small cell carcinoma (5%), chondosarcoma (2.5%) and malignant fibrous histocytoma (2.5%). Radiological finding with bone destruction (12.5%), without bone destruction (87.5%), intracranial involvement (45%) and orbital extension (17.5%). Conclusion: From the review of the series it is obvious that sinonasal malignancy usually presented at advanced stage with multiple sinus involvement. In case of single sinus involvement maxillary antral carcinoma is significantly common than other sinuses. Key words: Topographical Distribution; Sinonasal Malignancy. DOI: 10.3329/bjo.v17i1.7619 Bangladesh J Otorhinolaryngol 2011; 17(1): 21-28